Intraoperative Frozen Section Diagnosis of Adenoid Cystic Carcinoma of the Minor Salivary Gland: A Case Report - Mustika Sari; Noza Hilbertina (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Adenoid cystic carcinoma (ACC) is a rare malignant tumor of the salivary glands known for its slow growth, invasive behavior, and propensity for perineural invasion. The diagnosis of ACC can be challenging, especially during intraoperative frozen section consultation. This case report highlights the crucial role of frozen section diagnosis in guiding surgical management and ensuring tumor-free margins, which are critical for patient prognosis. Case presentation: A 44-year-old male presented with a slow-growing, occasionally painful nodule on his upper lip, without facial numbness or other systemic symptoms. A frozen section examination was performed intraoperatively to assess the lesion and determine the margin status. The frozen section revealed malignancy, characterized by tumor cell proliferation in tubular, cribriform, and solid patterns, all hallmarks of ACC, along with perineural invasion. A wide excision was performed, and subsequent frozen sections of the surgical margins confirmed they were free of tumor. The diagnosis of ACC was confirmed on histopathological examination of the paraffin block. Conclusion: This case underscores the importance of frozen section diagnosis in the management of ACC of the minor salivary glands. The accurate assessment of the lesion and margin status during surgery allows for appropriate surgical decision-making, ensuring complete tumor removal and minimizing the risk of recurrence.